2006
DOI: 10.1111/j.1468-5884.2006.00312.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of arachidonic acid on the spatial cognition of aged rats

Abstract: To examine the effects of arachidonic acid (AA) on age-related cognitive deficits, Fischer 344 rats were given an AA-supplemented powder diet for 12 weeks from 18.6 months old as part of the old AA (OA) group. Other age-matched rats were fed a non-AA-supplemented powder diet as part of the old control (OC) group, and young rats were fed lab pellets as part of the young control (YC) group. When the aged rats reached 20.0 months old, all animals were tested for spontaneous activity in an open field, followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…In vertebrates, arachidonic acid has been linked to memory enhancement rather than forge ng. Specifically, supplemen ng rat diets with arachidonic acid has been reported to protect against anesthesia-induced memory deficits (Li et al, 2015) and restores age-related declines in spa al memory (Okaichi et al, 2006(Okaichi et al, , 2005 and LTP maintenance (McGahon et al, 1997). In contrast, we observed that blocking arachidonic acid release with 4-BPB may slow forge ng, sugges that arachidonic acid func ons in Aplysia to reduce the expression of sensi za on memory.…”
Section: Discussionmentioning
confidence: 52%
“…In vertebrates, arachidonic acid has been linked to memory enhancement rather than forge ng. Specifically, supplemen ng rat diets with arachidonic acid has been reported to protect against anesthesia-induced memory deficits (Li et al, 2015) and restores age-related declines in spa al memory (Okaichi et al, 2006(Okaichi et al, , 2005 and LTP maintenance (McGahon et al, 1997). In contrast, we observed that blocking arachidonic acid release with 4-BPB may slow forge ng, sugges that arachidonic acid func ons in Aplysia to reduce the expression of sensi za on memory.…”
Section: Discussionmentioning
confidence: 52%
“…In vertebrates, arachidonic acid has been linked to memory enhancement rather than forgetting. Specifically, supplementing rat diets with arachidonic acid has been reported to protect against anesthesia-induced memory deficits ( Li et al, 2015 ) and restores age-related declines in spatial memory ( Okaichi et al, 2006 , 2005 ) and LTP maintenance ( McGahon et al, 1997 ). In contrast, we observed that blocking arachidonic acid release with 4-BPB may slow forgetting, suggesting that arachidonic acid functions in Aplysia to reduce the expression of sensitization memory.…”
Section: Discussionmentioning
confidence: 99%